Acoustic and thermal characterization of agar based phantoms used for evaluating focused ultrasound exposures - Menikou, Georgios; Damianou, Christakis A. (My University, 2017)
Background This study describes a series of experimental work completed towards characterizing candidate materials for fabricating brain and muscle tissue mimicking phantoms. Methods The acoustic speed, attenuation, impedance, thermal diffusivity, specific heat and thermal conductivity were measured. Results The resulting brain (2% w/v agar-1.2% w/v Silica Dioxide-25%v/v evaporated milk) and muscle tissue recipe (2% w/v agar-2% w/v Silica Dioxide-40%v/v evaporated milk) introduced a total attenuation coefficient of 0.59 dB/cm-MHz and 0.99 dB/cm-MHz respectively. Acrylonitrile Butadiene Styrene (ABS) possessed an attenuation coefficient of 16 dB/cm at 1 MHz which was found within the very wide range of attenuation coefficient values of human bones in literature. The thermal conductivity of the brain tissue phantom was estimated at 0.52 W/m°C and at 0.57 W/m.°Cfor the muscle. These values demonstrated that the proposed recipes conducted heat similar to the majority of most soft tissues found from bibliography. The soft tissue phantoms were also evaluated for their thermal repeatability after treating them repeatedly at different locations with the same sonication protocol and configuration. The average coefficient of variation of the maximum temperature at focus between the different locations was 2.6% for the brain phantom and 2.8% for the muscle phantom. Conclusions The proposed phantom closely matched the acoustic and thermal properties of tissues. Experiments using MR thermometry demonstrated the usefulness of this phantom to evaluate ultrasonic exposures.
Keywords: Ultrasound; Agar; Attenuation; Conductivity